The greatest speeches of all time (U.S.A Nosltalgia Company, 1998)
The Greatest Speeches of All-Time" is a collection of the most important and well-known speeches of modern times. These are the dramatic words from world leaders that changed the course of history and inspired millions worldwide. Franklin Delano Roosevelt, Sir Winston Churchill, General Douglas MacArthur, Harry S. Truman, John F. Kennedy, Rev Martin Luther King, Robert F. Kennedy, Malcolm X, Richard M. Nixon and Ronald Reagan.
Unabridged
Keywords: Speeches